MELATIH KETERAMPILAN GENERIK PADA SAINS DENGAN PEMBELAJARAN BERBASIS KONTEKSTUAL PADA MATERI CAHAYA KELAS VIII.2 MTs N ANDALAN PEKANBARU - Aryani, Dila Rizki; ', Zuhdi Ma’uf; ', Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to train generic science skills with contextual learning in science teaching physics class VIII MTs N Andalan Pekanbaru. This research was conducted in MTs N Andalan Pekanbaru in March to June 2016 for 4 months with the subject of VIII.2 class consisting of 35 students to 15 male students and 20 female students. Type of research is Pre Experimental Design with One Shot Case Study. Instruments of data collection in this study is a generic skill achievement test consisting of 10 indicators of generic skills in science are 20 questions given after the application of contextual learning. Data were analyzed descriptively. Descriptive analysis of generic skills of students after learning with contextual approach application got a good result. In the symbolic language generic skills earned an average of 89.6, on mathematical modeling skills earned an average of 79.0 and the generic skills of logical consistency earned an average of 66.2. So the contextual learning can be applied to train generic skills of students in the class VIII.2 MTs N Andalan Pekanbaru.Key Words: Generic Skills, Contextual Learning